2020
DOI: 10.17533/udea.ikala.v25n01a05
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Collaborative and Non- Collaborative Approaches to Teaching Reading Strategies on Iranian efl Learners’ Reading Comprehension and Attitude toward Reading

Abstract: In an efl context reading is a very important skill in language learning. This study aims at finding if instruction of reading strategies in two different collaborative and non-collaborative approaches affects reading comprehension and attitude toward reading differently. Forty-five Iranian adult female efl learners at pre intermediate general English proficiency level in Iran Language Institute (ili) were selected and divided into three groups of 15 students. One group functioning as the control group did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Martínez, Aricak, and Jewell [26] also claimed that high and low proficiency adolescent readers did not show statistical differences in reading attitude scores. Similarly, a study [27] reported that there were similar reading attitudes regardless of reading abilities, showing that students' reading attitude was not in line with reading achievement.…”
Section: Introductionmentioning
confidence: 96%
“…Martínez, Aricak, and Jewell [26] also claimed that high and low proficiency adolescent readers did not show statistical differences in reading attitude scores. Similarly, a study [27] reported that there were similar reading attitudes regardless of reading abilities, showing that students' reading attitude was not in line with reading achievement.…”
Section: Introductionmentioning
confidence: 96%